Excel data analysis for dummies - Nelson, Stephen L., 1959-; Nelson, E. C. (Elizabeth C.) (--For dummies., 2016)
"Put the power of Excel to work and excel at data analysis! Most businesses are drowning in data, and making sense of it all is critical. Excel is a powerful data analysis tool, and this books shows you how to use it and become a data deciphering expert. You'll learn to organize data in workbooks, create powerful magic with PivotTables and PivotCharts, and explore advanced statistical tools that take you to the next level." -- Back cover.